QIYAS ANALYSIS AS A LEGAL ISTINBATH METHOD AND ITS IMPLEMENTATION IN SHARIA ECONOMIC LAW - Muchlis Bahar (Jurnal Kelola: Jurnal Ilmu Sosial, 2018)
The purpose of this study was to analyze qiyas as a legal istinbath method and its relevance to Islamic economics. This study uses a qualitative method with a library research approach. The type of research data used is secondary data. The research data is presented qualitatively-descriptively. Based on the results of the study, it can be concluded that qiyas has four main pillars, namely ashl, far, 'illat, and original law. So in the development of Islamic economics, qiyas as a legal istinbath method has applications in various ways, including in leasing (ijarah) with buying and selling, qiyas Ajir (people who rent out their labor) with al-wakil bil ujrah (people who are given authority in exchange for wages), qiyas khiyar naqd with khiyar syarth, qiyas bank interest on the practice of usury, and qiyas the practice of money changer which is qiyas by buying and selling medium of exchange.